Impact of Climate Change on Vector-Borne Diseases in Wildlife - Nafuna, Kate (Animal Health Journal, 2024)
Purpose: This study sought to investigate the impact of climate change on vector-borne diseases in wildlife. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to climate change on vector-borne diseases in wildlife. Preliminary empirical review revealed that that environmental shifts, driven by climate change, profoundly influenced the distribution and transmission dynamics of diseases among wildlife populations. Through a comprehensive review of empirical studies, it was found that warmer temperatures, altered precipitation patterns, and extreme weather events expanded vector habitats, increasing disease exposure for wildlife. The research emphasized the importance of interdisciplinary approaches and proactive measures, such as habitat restoration and disease surveillance, to mitigate disease risks and promote ecosystem resilience. Overall, the study highlighted the urgent need to address the interconnected challenges of climate change, vector-borne diseases, and wildlife health to safeguard environmental and human well-being. Unique Contribution to Theory, Practice and Policy: The Ecological Niche theory, Disease Ecology theory and One Health theory may be used to anchor future studies on climate change on vector-borne diseases in wildlife. The study provided recommendations that contributed to theory, practice, and policy. From a theoretical perspective, it emphasized the need for interdisciplinary research to understand the complex interactions between climate change, vector populations, and disease transmission. Practically, the study recommended adaptive management strategies, such as habitat restoration and disease surveillance, to mitigate disease risks in wildlife. Policy-wise, it called for integrating climate resilience and biodiversity conservation efforts, along with public education campaigns and international cooperation, to address the transboundary nature of vector-borne disease threats. Overall, these recommendations aimed to build resilience in ecosystems, protect biodiversity, and ensure the health of wildlife populations amidst climate change.